The Application of Trigonometry on Problem Solving Strategy - Ratnasari, Gamarina Isti (Proceeding International Conference on Science and Engineering, 2020)
This study aims to: (1) describe students’ problem solving strategies to solve trigonometric problems using a clinometer media and (2) comparison of the strategies used against student analysis in processing the data obtained. This type of research uses qualitative research. The population of this study was all students of class X consisting of 7 classes, with 39 research subjects. Data collection is done by direct observation of the results of student work. The results showed that (1) students’ problem solving strategies to solve trigonometric problems using a clinometer media were divided into two strategies: students pay attention to angular size rather than distance and students pay attention to distance than angular size to determine the height of an object and (2) the strategy used students paying attention to angles rather than distance show more accurate results when students use angles than students pay attention to distances rather than angles to determine the height of an object.